Effect of organic amendments on the productivity and quality of produce and soil in groundnut (Arachis hypogaea)-onion (Allium cepa) cropping system - LATHA, H S; SHARANAPPA (The Indian Journal of Agricultural Sciences, 2014)
Field experiments was conducted during 2010-12 at Bangalore to study the effect of sources on the quality of soil, crop and sustainability of yield in groundnut (Arachis hypogaea L.) onion (Allium cepa L.) cropping system involving biodigested liquid organic manure (BDLM), enriched biodigested liquid organic manure (EBDLM),cow urine (CU) vis-a-vis recommended doses of fertilizers for irrigated groundnut (FYM at 10 tonnes + 25:75:37.5 kg N:P2O5:K2O/ha) and onion (FYM at 30 tonnes + 125:50:75 kg N:P2O5:K2O/ha) with three foliar sprays of panchagavya (PG) and vermiwash (3 percent) at 30, 60 and 75 days after sowing. Application of EBDLM at 25 kg N equivalent/ ha + 3 sprays of 3% PG for groundnut, EBDLM at 125 kg N equivalent/ha + 3 sprays of PG at 3% for onion registered significantly higher organic carbon content and available nitrogen, phosphorus, potassium and sulphur (0.63%, 355.2, 78.30, 190.8 and 36.3 kg/ha, respectively) and significantly more number of bacteria (32.58 × 106CFU / g of soil), fungi (21.77 × 103 CFU/g of soil) and actinomycetes (12.28 × 103CFU/g of soil) after the harvest of second crop in groundnut-onion sequence cropping system. Pod yield of groundnut (2335 kg/ha) and bulb yield of onion (37.78 tonnes/ha) were significantly higher with the application of EBDLM at 25 kg N equivalent/ha + 3 sprays of PG at 3% (groundnut)/ EBDLM at 125 kg N equivalent/ha + 3 sprays of 3% PG (onion). Sustainability yield index was also higher with above treatment (0.90 and 0.89 for groundnut and onion, respectively). Quality parameters like oil and protein yield (875 and 364 kg /ha, respectively) in groundnut and total soluble solids, reducing, non-reducing sugars, ascorbic and pyruvic acid (16.93, 3.66, and 8.66%, 25.27 mg 100/g and 12.82 Î¼ moles/g, respectively) of onion bulb were significantly superior with above treatment.